Análise comparativa da sustentabilidade das tecnologias de produção leiteira na agricultura familiar: manejo do pastoreio racional Voisin e balde cheio: um estudo no Território da Cantuquiriguaçú – PR. - Lima, Juliano Antunes de (2017)
Milk activity in Brazil has strong traits of family agriculture, and such activity is extremely relevant for the economy of these families, as well as for their social identity as Family Farmers. The Cantuquiriçuçu Territory in the state of Paraná is characterized by the presence of family farmers who produce milk from various technologies, including the Voisin Rational Grazing (VRG) and “Balde Cheio”. The integration of industry with agriculture often makes farmers dependent on external inputs, which often end up economically crippling production and polluting the environment; on the other hand, there are agroecological production techniques based on sustainable agricultural systems that allow free production from agrochemicals and ensure the nutritional quality of food and are more profitable per unit produced than conventional ones. In this sense, the present study aims to characterize the economic, social and environmental sustainability of milk production technologies under VRG and “Balde Cheio” management. The descriptive research was carried out through a multi case study, implemented in eight properties, four of which used VRG and four used “Balde Cheio”. Interviews were conducted with the owners in order to collect data regarding the use of VRG and “Balde Cheio” technologies. The interview script was built considering three asprcts: economic, social and environmental. For economic and social analysis, the Agrarian Systems Diagnostic Analysis (ASDA) method was used to demonstrate the Social Reproduction Level (SRL) reached by each production unit. The environmental dimension was measured by the adoption of Agroecological Practices developed in each production unit demonstrating the percentage of adherence of each producer to Agroecology. The results pointed out that the production units that work with the VRG technology showed greater adherence to Agroecology, less dependence on external industrial inputs and lower costs. In the NRS eighty percent of the production units reached and surpassed the established level. The “Balde Cheio” technology presented higher financial results such as Gross Production and higher NRS in relation to VRG, however, higher costs and greater risks in relation to market price and consumption of external inputs.